EVALUASI NILAI BIOLOGIS PAKAN LENGKAP BERBASIS TEBON JAGUNG DAN RUMPUT CAMPURAN TERHADAP KINERJA PRODUKSI SAPI PERANAKAN ONGOLE (PO) - Tulung, Yohannis L.R.; Pendong, A.F.; Tulung, B. (ZOOTEC, 2020)
EVALUATION OF BIOLOGICAL VALUE OF COMPLETE FEED BASED ON CORN COB AND MIXED GRASS ON PRODUCTION PERFORMANCE OF ONGOLE. This study was aimed to obtain the feed formula, which is effective on the productivity of beef cattle (PO). This study consisted of two experimental stages, namely: 1). In vitro experiment, and 2). Biological (in vivo) experiment. t-test two sample assuming unequal variance was used as the statistical analysis on both experiments. The treatments of this research consisted of RA feed = 50% concentrate + 50% corn forage and RB feed = 50% concentrate + 50% mixed grass, and it was repeated 10 times. In vitro test was used to measure dry matter and organic matter digestibility and NH3 concentration (NH3). The biological experiment (in vivo) was used 20 PO cattles, 12-18 months of ages, with 120 - 180 kg of body weight to measure feed intake, nutrients digestibility DMD, OMD, Protein and energy digestibility, live weight gain (LWG) and feed conversion (FCR). The results showed DMD and OMD in vitro of RA were 67.88% dan 66.06%, respectively, lower than the DMD and OMD obtained in RB, i.e 71.15% dan 69.08%, respectively. Meanwhile, NH3 of RA was higher than RB, i.e: 3.20 vs 2.50 mM/L. The biological experiment showed the DMD, OMD, CPD, and DE (in vivo) of RA were 77.05%, 78.64%, 82.13%, and 83.48%, respectively, while the results obtained at RB were higher, i.e. 80.15%, 83.44%, 85.55%, and 87.46%, respectively. On the liveweight gain (LWG) of PO cattle, the RA ration produces 0.60 kg per head per day, lower than RB which produces 0.65 kg per head per day. The FCR of both ration was 0.11. It is concluded, complete feed based on forage corn and mixed grass can be used as standard feed for fattening of local beef cattle because it is able to give high nutrient digestibility and good feed conversion valueÂ Keywords: Complete feed, in vitro and in vivo digestibility, liveweight gain, feed conversion